Controlling sudden transition between classical and quantum decoherence via squeezing phase of the baths. (4th May 2021) - Basit, Abdul; Ali, Hamad; Badshah, Fazal; Yang, Xiao-Fei; Ge, Guo-Qin
Abstract: Correlations in the open quantum systems exhibit a rich phenomenology in various decoherent environments. We theoretically study the dynamics of quantum and classical correlations in a two-qubit system, where each qubit is locally subjected to the relevant squeezed vacuum bath through the non-demolition interaction. Specifically, we unveil the effects of the squeezing phase of the bath and squeezing strength on the intriguing phenomena of freezing discord and sudden transition between classical and quantum decoherence. Remarkably, we show that by proper tuning the squeezing phase one can significantly delay the sudden transition time t ′ . Interestingly, we found that the maximum delay in t ′ may obtain when the phase difference between the squeezing phase and the phase of the coupling strength is π /2. Consequently, an increase in the t ′ leads to the enhancement of time-interval during which quantum discord does not affect by environmental noise. On the other hand, we show that squeezing strength plays a negative role in enhancing sudden transition time and preserving quantum discord. Furthermore, we also show that squeezed bath allows the existence of the time-invariant discord for a broader range of Ohmicity parameter s and initial condition ε . Strikingly our study renders new insights to control and sustain quantum correlations against the detrimental effects of decoherence beyond the conventional protocols.